How Pantomime Works: Implications for Theories of Language Origin - Brown, Steven; Mittermaier, Emma; Kher, Tanishka; Arnold, Paul (Frontiers in Communication, 2019)
Pantomime refers to iconic gesturing that is done for communicative purposes in the absence of speech. Gestural theories of the origins of language claim that a stage of pantomime preceded speech as an initial form of referential communication. However, gestural theories conceive of pantomime as a unitary process, and do not distinguish among the various means by which it can be produced. We attempt here to develop a scheme for classifying pantomime based on a proposal of two new sub-categories of pantomime, resulting in a final scheme comprised of five categories of iconic gesturing. We employ the scheme to establish associations between the category of pantomime used and the type of action and/or object being depicted. Based on these associations, we argue that there are two basic modes of pantomiming and that these apply to distinct semantic categories of referents. These modes of pantomiming lead to two alternative models for a gestural origin of language, one based on people and one based on the environment.